1989
DOI: 10.1128/jvi.63.7.3051-3056.1989
|View full text |Cite
|
Sign up to set email alerts
|

T-cell-mediated clearance of mouse hepatitis virus strain JHM from the central nervous system

Abstract: Clearance of the neurotropic JHM strain of mouse hepatitis virus from the central nervous system was examined by the transfer of spleen cells from immunized donors. A T cell with the surface phenotype of Thy1.2+ CD4+ CD8- asialo-GM1+ Mac-1- was found to be necessary for viral clearance. The surface phenotype and adherence to nylon wool suggest that these cells are activated helper-inducer T cells. Adoptive transfer to congenic histocompatibility strains demonstrated the necessity for compatibility at the D loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
55
1

Year Published

1992
1992
2002
2002

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(65 citation statements)
references
References 39 publications
9
55
1
Order By: Relevance
“…Further, the clearance of virus requires compatibility between donor and recipient at the major histocompatibility complex (MHC) Class 1 genes. These data also indicated that a CD4+ helperT cell is required for the activation of the CD8+ effecters (Sussman et al, 1989). This dependence on CD4+ T cells has been confirmed by the in viva depletion of CD4+ and CD8' T cells (Williamson and Stohlman, 1990).…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…Further, the clearance of virus requires compatibility between donor and recipient at the major histocompatibility complex (MHC) Class 1 genes. These data also indicated that a CD4+ helperT cell is required for the activation of the CD8+ effecters (Sussman et al, 1989). This dependence on CD4+ T cells has been confirmed by the in viva depletion of CD4+ and CD8' T cells (Williamson and Stohlman, 1990).…”
Section: Introductionmentioning
confidence: 56%
“…CytotoxicT lymphocytes (CTL) are an important component of the immune response to many viral infections. CTL have been implicated in the pathogenesis of MHV infection by the demonstration that a reduction in JHMV titer during infection of C57Bl/6 mice requires a CD8+ T cell (Sussman et al, 1987(Sussman et al, , 1989. Further, the clearance of virus requires compatibility between donor and recipient at the major histocompatibility complex (MHC) Class 1 genes.…”
Section: Introductionmentioning
confidence: 99%
“…Following the inoculation of the JHM strain of mouse hepatitis virus (JHMV) into susceptible mice, for example, an acute encephalomyelitis is elicited with robust infection of astrocytes, oligodendrocytes, and, to a lesser degree, neurons. Using an adoptive transfer strategy, viral clearance from the brains of these hosts has been shown to be mediated by an H2-D-restricted, virus-specific CD8 ÷ T cell population (Sussman et al, 1989). Interestingly, these CD8 ÷ CTLs have an absolute requirement for CD4+ T cells that appear to support their local survival within the brain (Stohlman et al, 1998).…”
Section: B T Cells Promote Clearance Of Viruses From Brainmentioning
confidence: 99%
“…Weiss in JHM-infected mice and that CD8 + , major histocompatibility complex (MHC) class I-restricted T cells are important in viral clearance . [6][7][8][9] In addition, MHC class (restricted T cells, possibly suppressor/cytotoxic T cells (CTL), have been isolated from mice infected with JHM . 10, "…”
Section: Introductionmentioning
confidence: 99%